Math and Science Teacher Candidates’ Use of Technology to Facilitate Teaching and Learning During Student Teaching - Tassell, Janet; Stobaugh, Rebecca Ruth; McDonald, Michael (Educational (Re)naissance, 2013)
The goal of this study is to determine how effectively student teachers from a large comprehensive institution have used technology to compliment their teaching in mathematics and science. The researchers reviewed the required Teacher Work Sample (TWS) capstone projects of student teachers. The TWS is an authentic assessment instrument designed to guide student teachers in designing, implementing, reviewing, and adjusting instruction. The TWS document narratives articulated the use of technology, and this use was compared to the 2008 U.S. Department of Education (USDE): Measures of Teacher and Student Technology Use. Data gathered in the study revealed both strengths and weaknesses regarding the student teachers’ use of technology to enhance their teaching goals.